Almost just friends eaudiobook A novel. - Shalvis, Jill (Wildstone, 2020)
New York Times bestselling author Jill Shalvis returns to Wildstone with the touching story of finding your place in the world—and the people who make it home. Piper Manning's about as tough as they come, she's had to be. She raised her siblings and they've thankfully flown the coop. All she has to do is finish fixing up the lake house her grandparents left her, sell it, and then she's free. When a massive storm hits, she runs into a tall, dark and brooding stranger, Camden Reid. There's a spark there, one that shocks her. Surprising her further, her sister and brother return, each of them holding their own secrets. The smart move would be for Piper to ignore them all but Cam unleashes emotions deep inside of her that she can't deny, making her yearn for something she doesn't understand. And her siblings...well, they need each other. Only when the secrets come out, it changes everything Piper thinks she knows about her family, herself...and Cam. Can she find a way to outrun the demons? The answer is closer than she thinks—just as the new life she craves may have already begun.